New half-sandwich ruthenium(ii) complexes as proteosynthesis inhibitors in cancer cells. Issue 8 (11th January 2019) - Ballester, Francisco J.; Ortega, Enrique; Porto, Vanesa; Kostrhunova, Hana; Davila-Ferreira, Nerea; Bautista, Delia; Brabec, Viktor; Domínguez, Fernando; Santana, M. Dolores; Ruiz, José
Abstract : New Ru(ii ) arene anticancer complexes with a non-coordinated CHO group that are able to inhibit the protein synthesis; this is a new mode of action for half-sandwich metal complexes. Abstract : Half-sandwich ruthenium(ii ) complexes [(η 6 - p -cymene)Ru(C^N)-(X)] 0/+ (X = Cl, py or 4-NMe2 -py) containing a cyclometalated 2-ppy or 1-ppz with a non-coordinated CHO group as a handle for further functionalization have been synthesized to achieve selective cytotoxicity to cancer cells, the more potent compounds acting as proteosynthesis inhibitors; this is a new mode of action for half-sandwich metal complexes.